Stimulatory effects of Mn-embedded root plaques on N2O emissions from paddy soil depend on light intensity - Wei Song; Jinzhi Yao; Yingdong Fu; Yuying Li; Chaoqun Wang; Timothy Clough; Zhenjie Shi; Shuping Qin (Bioresource Technology, 2026)

Brachiopods and associated skeletal taxa from the early Cambrian of southeastern Shaanxi, South China - Mei Luo; Timothy P. Topper; Guoxiang Li; Baopeng Song; Zhao Wang; Caibin Zhang; Jingliang Zhao; Peiyao Wang; Rao Fu; Fan Liu; Zhifei Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Leached Nitrate Reduces the Abundance of Antibiotic Resistance Genes in Deep Soil Layers up to 10 m - Wei Song; Jinzhi Yao; Timothy Clough; Yingdong Fu; Hanpeng Liao; Chunsheng Hu; Chaoqun Wang; Shuping Qin (Environmental Microbiology, 2026)
Antibiotic resistance genes (ARGs) represent a threat to human health. Factors impacting ARGs have been well studied in surface soils, but how such factors affect ARGs in deep soils (> 2 m) remains unknown. This in situ study investigated how long‐term excessive nitrogen (N) fertilisation, specifically leached nitrate (NO 3 − ), influenced ARGs up to 10 m depth. Under replicated 26‐year fertilisation (600 kg N ha −1 ) plots, significant reductions (10%–65%) were observed across multiple ARG classes, including beta‐lactam, fluoroquinolone, glycopeptide, macrolide‐lincosamide‐streptogramin (MLS), multidrug, and rifamycin resistance genes, correlating with elevated NO 3 − concentrations. KEGG pathways related to antibiotic biosynthesis and the relative abundance of S‐strategy ARG hosts, such as Achromobacter , were both reduced. Additionally, network analysis revealed more positive and fewer negative microbial associations under N treatment. These findings suggest that NO 3 − leaching alleviates microbial N limitation, modulates ecological strategies and microbial interaction networks, and ultimately contributes to lower ARG abundance in deep soil layers.

Repeat duplication and divergence in the linusorb-related gene family in flax (Linum usitatissimum) - Ziliang Song; Timothy F. Sharbel; Yong Wang; Martin J.T. Reaney (Food Bioscience, 2025)

Revising the coal mining CH4 emission factor based on multiple inventories and atmospheric inversion approach at one of the world's largest coal production areas: Shanxi province, China - Xuejing Shi; Yiyi Peng; Shumin Wang; Yifan Zhang; Junqing Zhang; Hao Song; Yu Cui; Fan Sun; Huili Liu; Qitao Xiao; Ning Hu; Wei Xiao; et al. (Science of The Total Environment, 2025)

Ref-1 is overexpressed in neovascular eye disease and targetable with a novel inhibitor - Anbukkarasi Muniyandi; Gabriella D. Hartman; Kamakshi Sishtla; Ratan Rai; Cátia Gomes; Kristina Day; Yang Song; Andi R. Masters; Sara K. Quinney; Xiaoping Qi; Hailey Woods; Michael E. Boulton; et al. (Angiogenesis, 2025)

Cenozoic intracontinental tectonics of Mongolia and its climate effects: A synthesized review - Ulambadrakh Khukhuudei; Timothy Kusky; Brian F. Windley; Orolzodmaa Otgonbayar; Lu Wang; Jungsheng Nie; Wenjiao Xiao; Lei Zhang; Xiaodong Song (Earth-Science Reviews, 2024)

On the transferability of residence time distributions in two 10-km long river sections with similar hydromorphic units - Jie Bao; Xuehang Song; Yunxiang Chen; Yilin Fang; Xinming Lin; Zhangshuan Hou; Zhuoran Duan; Huiying Ren; William Perkins; Xiaoliang He; Timothy Scheibe (Journal of Hydrology, 2024)

Thermodynamic control on the decomposition of organic matter across different electron acceptors - Jianqiu Zheng; Timothy D. Scheibe; Kristin Boye; Hyun-Seob Song (Soil Biology and Biochemistry, 2024)

Nitrate-induced hydroxyl radical releases deep soil organic carbon by opening the ‘enzyme latch’ under micro-aerobic conditions - Wei Song; Timothy Clough; Honghuan Hou; Shuping Qin (Soil Biology and Biochemistry, 2024)

Microbial defluorination of TFA, PFOA, and HFPO-DA by a native microbial consortium under anoxic conditions - Zhiwen Tang; Timothy M. Vogel; Qing Wang; Changlong Wei; Mukhtiar Ali; Xin Song (Journal of Hazardous Materials, 2024)

Spartina alterniflora invasion differentially alters microbial residues and their contribution to soil organic C in coastal marsh and mangrove wetlands - Xueli Ding; Weiqi Wang; Jiahui Wen; Tianshu Feng; Josep Peñuelas; Jordi Sardans; Chao Liang; Evgenios Agathokleous; Chun Wang; Zhaoliang Song; Qiang Li; Timothy R. Filley; et al. (CATENA, 2023)

Does neighborhood or residence influence continued smoking among cancer patients: a spatial-ecological and descriptive analyses brief report - Kimlin T. Ashing; Gaole Song; Brian Tiep; Cary Presant; Udochukwu Obodo; Jonjon Macalintal; Sophia Yeung; Jossie Sandoval; Timothy O’Connor (Cancer Causes & Control, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Proceedings of the fifth international Molecular Pathological Epidemiology (MPE) meeting - Song Yao; Peter T. Campbell; Tomotaka Ugai; Gretchen Gierach; Mustapha Abubakar; Viktor Adalsteinsson; Jonas Almeida; Paul Brennan; Stephen Chanock; Todd Golub; Samir Hanash; Curtis Harris; et al. (Cancer Causes & Control, 2022)

Roots and microbiome jointly drive the distributions of 17 phytohormones in the plant soil continuum in a phytohormone‐specific manner - Yuqiu Lu; Enzhao Wang; Zhiyu Tang; Junpeng Rui; Yanling Li; Zhixi Tang; Weiling Dong; Xiongduo Liu; Timothy S. George; Alin Song; Fenliang Fan (Plant and Soil, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Effective detection methods for Pectinatella magnifica Leidy 1851 colony distribution using statoblasts - Eui-Jeong Ko; Yuno Do; Hojoon Kim; Haeng-Seop Song; Timothy S. Wood; Tae-Soo Chon; Gea-Jae Joo; Ji Yoon Kim (Biological Invasions, 2021)

Spartina alterniflora invasion controls organic carbon stocks in coastal marsh and mangrove soils across tropics and subtropics - Shaopan Xia; Weiqi Wang; Zhaoliang Song; Yakov Kuzyakov; Laodong Guo; Lukas Van Zwieten; Qiang Li; Iain P. Hartley; Yuanhe Yang; Yidong Wang; Timothy Andrew Quine; Congqiang Liu; et al. (Global Change Biology, 2021)
Coastal wetlands are among the most productive ecosystems and store large amounts of organic carbon (C)—the so termed “blue carbon.” However, wetlands in the tropics and subtropics have been invaded by smooth cordgrass ( Spartina alterniflora ) affecting storage of blue C. To understand how S. alterniflora affects soil organic carbon (SOC) stocks, sources, stability, and their spatial distribution, we sampled soils along a 2500 km coastal transect encompassing tropical to subtropical climate zones. This included 216 samplings within three coastal wetland types: a marsh ( Phragmites australis ) and two mangroves ( Kandelia candel and Avicennia marina ). Using δ 13 C, C:nitrogen (N) ratios, and lignin biomarker composition, we traced changes in the sources, stability, and storage of SOC in response to S. alterniflora invasion. The contribution of S. alterniflora ‐derived C up to 40 cm accounts for 5.6%, 23%, and 12% in the P. australis , K. candel , and A. marina communities, respectively, with a corresponding change in SOC storage of +3.5, −14, and −3.9 t C ha −1 . SOC storage did not follow the trend in aboveground biomass from the native to invasive species, or with vegetation types and invasion duration (7–15 years). SOC storage decreased with increasing mean annual precipitation (1000–1900 mm) and temperature (15.3–23.4℃). Edaphic variables in P. australis marshes remained stable after S. alterniflora invasion, and hence, their effects on SOC content were absent. In mangrove wetlands, however, electrical conductivity, total N and phosphorus, pH, and active silicon were the main factors controlling SOC stocks. Mangrove wetlands were most strongly impacted by S. alterniflora invasion and efforts are needed to focus on restoring native vegetation. By understanding the mechanisms and consequences of invasion by S. alterniflora , changes in blue C sequestration can be predicted to optimize storage can be developed.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

SsHKT1;1 is coordinated with SsSOS1 and SsNHX1 to regulate Na+ homeostasis in Suaeda salsa under saline conditions - Wen-Ying Wang; Ya-Qi Liu; Hui-Rong Duan; Xiu-Xia Yin; Yan-Nong Cui; Wei-Wei Chai; Xin Song; Timothy J. Flowers; Suo-Min Wang (Plant and Soil, 2020)

A Qualitative Systematic Review of Cigarette Smoking Cessation Interventions for Persons Living with HIV - Lilli Mann-Jackson; David Choi; Erin L. Sutfin; Eunyoung Y. Song; Kristie L. Foley; Aimee M. Wilkin; Caryn G. Morse; Nicole F. Rojas; Timothy S. Oh; Scott D. Rhodes (Journal of Cancer Education, 2019)

Proceedings of the fourth international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Christine B. Ambrosone; Reiko Nishihara; Hugo J. W. L. Aerts; Melissa Bondy; Nilanjan Chatterjee; Montserrat Garcia-Closas; Marios Giannakis; Jeffrey A. Golden; Yujing J. Heng; N. Sertac Kip; Jill Koshiol; et al. (Cancer Causes & Control, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Zircon and Monazite Ages Constraints on Devonian Magmatism and Granulite-Facies Metamorphism in the Southern Qaidam Block: Implications for Evolution of Proto- and Paleo-Tethys in East Asia - Jin Ba; Lu Zhang; Chuan He; Neng-Song Chen; Timothy M. Kusky; Qinyan Wang; Yusheng Wan; Xiaoming Liu (Journal of Earth Science, 2018)

Assessing the interplay between canopy energy balance and photosynthesis with cellulose δ18O: large-scale patterns and independent ground-truthing - Brent R. Helliker; Xin Song; Michael L. Goulden; Kenneth Clark; Paul Bolstad; J. William Munger; Jiquan Chen; Asko Noormets; David Hollinger; Steve Wofsy; Timothy Martin; Dennis Baldocchi; et al. (Oecologia, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Migration and leaching characteristics of base cation: indicating environmental effects on soil alkalinity in a karst area - Mingzhen Ma; Yang Gao; Xianwei Song; Sophie M. Green; Bailian Xiong; Jennifer A. J. Dungait; Tao Peng; Timothy A. Quine; Xuefa Wen; Nianpeng He (Environmental Science and Pollution Research, 2018)

Dynamical and thermodynamical coupling between the North Atlantic subtropical high and the marine boundary layer clouds in boreal summer - Wei Wei; Wenhong Li; Yi Deng; Song Yang; Jonathan H. Jiang; Lei Huang; W. Timothy Liu (Climate Dynamics, 2018)

Ecosystem service delivery in Karst landscapes: anthropogenic perturbation and recovery - Timothy Quine; Dali Guo; Sophie M. Green; Chenglong Tu; Iain Hartley; Xinyu Zhang; Jennifer Dungait; Xuefa Wen; Zhaoliang Song; Hongyan Liu; Heather Buss; Timothy Barrows; et al. (Acta Geochimica, 2017)

Proceedings of the third international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Timothy R. Rebbeck; Reiko Nishihara; Andrew H. Beck; Colin B. Begg; Alexei A. Bogdanov; Yin Cao; Helen G. Coleman; Gordon J. Freeman; Yujing J. Heng; Curtis Huttenhower; Rafael A. Irizarry; et al. (Cancer Causes & Control, 2017)

On the origin and evolution of apomixis in Boechera - John T. Lovell; Olawale M. Aliyu; Martin Mau; M. Eric Schranz; Marcus Koch; Christiane Kiefer; Bao-Hua Song; Thomas Mitchell-Olds; Timothy F. Sharbel (Plant Reproduction, 2013)

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

Evidence that herpes simplex virus DNA derived from quiescently infected cells in vitro , and latently infected cells in vivo , is physically damaged - Scott Millhouse; Ying-Hsiu Su; Xianchao Zhang; Xiaohe Wang; Benjamin P Song; Li Zhu; Emily Oppenheim; Nigel W Fraser; Timothy M Block (Journal of NeuroVirology, 2010)

Quantitative Diffusion Tensor Imaging Tractography Metrics are Associated with Cognitive Performance Among HIV-Infected Patients - David F. Tate; Jared Conley; Robert H. Paul; Kathryn Coop; Song Zhang; Wenjin Zhou; David H. Laidlaw; Lynn E. Taylor; Timothy Flanigan; Bradford Navia; Ronald Cohen; Karen Tashima (Brain Imaging and Behavior, 2010)